2022
DOI: 10.3390/cells11010140
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Metabolism in Cancer Drug Resistance

Abstract: Despite the numerous investigations on resistance mechanisms, drug resistance in cancer therapies still limits favorable outcomes in cancer patients. The complexities of the inherent characteristics of tumors, such as tumor heterogeneity and the complicated interaction within the tumor microenvironment, still hinder efforts to overcome drug resistance in cancer cells, requiring innovative approaches. In this review, we describe recent studies offering evidence for the essential roles of amino acid metabolism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 149 publications
0
32
1
2
Order By: Relevance
“…For example, the overexpression of the cystine transport system assists cancer cells in decreasing drug sensitivity. 79 …”
Section: Resultsmentioning
confidence: 99%
“…For example, the overexpression of the cystine transport system assists cancer cells in decreasing drug sensitivity. 79 …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that amino acid metabolism is related to drug resistance in cancer cells, as it regulates the TCA cycle and oxidative phosphorylation [ 45 ]. Additionally, several reports have indicated that inhibiting mTOR signaling can increase the sensitivity to paclitaxel [ 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Glutamin hücre biyolojisinde pleiotropik bir role sahiptir ve çeşitli kanser türlerinde bağımlılığı iyi bilinmektedir. Ayrıca, farmakolo jik müdahale veya glutamin metabolizmasının diyet modülasyonu umut verici bir terapötik yaklaşım olarak kabul edilir (23,24). Arjinin; yarı esansiyel bir amino asit olup, kanser hücresi büyümesi ve hayatta kalma ve bağışıklık hücresi işlevi gibi çeşitli biyolojik işlevlerde yer alır.…”
Section: Discussionunclassified
“…Arjinin; yarı esansiyel bir amino asit olup, kanser hücresi büyümesi ve hayatta kalma ve bağışıklık hücresi işlevi gibi çeşitli biyolojik işlevlerde yer alır. Bu nedenle, arginin mevcudiyetinin modülasyonu, metabolizmaya dayalı kanser tedavileri için umut verici bir terapötik strateji olarak vurgulanmaktadır (24).Yaptığımız çalışma sonucunda; sisplatin kanser hücrelerinde argininve glutamin aminoasitlerinde artışa yol açarken, normal hücrelerde bu aminoasitlerin azalmasına neden olmuştur.Sonuç olarak, kanserlerde ilaç direncini artırmada amino asit metabolizmasının temel rollerine ilişkin bilgiler, ilaç direncinin üstesinden gelmek için potansiyel terapötik yaklaşımları ortaya çıkarmıştır. Konvansiyonel kemoterapi ve ilgili toksisitenin gerekliliğini azaltmaya yardımcı olmak için amino asit metabolizmasının modülasyonu hakkında daha fazla araştırma yapılacağını umuyoruz.…”
Section: Discussionunclassified